Direct detection of magnetism with spectrointerferometry. Issue 69 (10th September 2015) - Perraut, K.; Le Bouquin, J.-B.; Chesneau, O.
Abstract : Stellar magnetism and activity are often studied thanks to various spectro-polarimetric techniques but generally the poor angular resolution drastically limits detection and/or diagnosis since the polarized signals are averaged over the stellar surface and thus can be cancelled because of symmetry degrees. Taking benefit of the unprecedent resolving power of optical long-baseline interferometry will be a significant gain, allowing the local polarized features to be studied. In this review we briefly describe the various methods that are classically used to detect and/or map magnetic fields, and then explain how optical interferometry can bring new and complementary observational information.